Chitosan / gelatin / PVA composite hydrogel as well as preparation method and application thereof

The cross-connected three-dimensional porous hydrogel is prepared by blending chitosan, gelatin with PVA and adding hydroxyapatite, which solves the problem of insufficient mechanical properties and biocompatibility of hydrogel materials, and realizes the versatility and efficiency of cartilage repair materials.

CN120361310AInactive Publication Date: 2025-07-25CHIZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510558901.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-30
Publication Date
2025-07-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing hydrogel materials have shortcomings in mechanical properties and biocompatibility and cannot meet the needs of cartilage repair.

Method used

The cross-connection three-dimensional porous hydrogel was prepared by blending chitosan, gelatin and PVA, combined with chemical cross-linking and physical cross-linking methods, and hydroxyapatite extracted from grass carp scales.

Benefits of technology

It improves the mechanical properties and biocompatibility of the hydrogel, provides a multifunctional material foundation, adapts to different repair needs, and has good thermal stability and water absorption properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120361310A_ABST
    Figure CN120361310A_ABST
Patent Text Reader

Abstract

The invention provides chitosan / gelatin / PVA composite hydrogel as well as a preparation method and application thereof, and relates to the technical field of biomedical materials. The preparation method comprises the following steps: uniformly mixing a chitosan solution, a gelatin solution, hydroxyapatite and polyvinyl alcohol (PVA) under a water bath condition, then adding a cross-linking agent for blending and cross-linking, and defoaming to obtain a mixed solution; and circularly freezing and thawing the mixed solution, and drying to obtain the chitosan / gelatin / PVA composite hydrogel. According to the invention, chitosan, gelatin and PVA are blended, and a chemical crosslinking and physical crosslinking combined mode is adopted, so that the defect of a single material is effectively made up. The hydrogel prepared by the invention has a crossed and communicated three-dimensional porous network structure, is uniform in pore size distribution and interpenetrating in pores, and meets the structural requirement of cartilage repair on a stent material. The composite hydrogel has mechanical strength, thermal stability, high water absorption and biocompatibility, the formula can be flexibly adjusted according to different repair requirements, and a multifunctional material basis is provided for cartilage tissue engineering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biomedical materials, and particularly relates to a chitosan / gelatin / PVA composite hydrogel, a preparation method thereof, and an application thereof. Background Art

[0002] Joints play an indispensable role in maintaining body balance and movement coordination. However, articular cartilage is often damaged due to local impact, strenuous exercise, body aging, and other pathological problems. Moreover, due to the very limited repair ability of cartilage, if not treated in time, it will continue to deteriorate and lead to osteoarthritis, seriously affecting the physical and mental health of patients.

[0003] Researchers have been deeply concerned about new methods for articular cartilage repair - cartilage tissue engineering technology. In recent years, in order to develop biomaterials that can replace or repair damaged natural cartilage, people have developed biomaterials that mimic articular cartilage from three aspects: the structure, function, and materials of natural articular cartilage. The biomimetic cartilage materials have high durability when applied to the human body. They have both a porous structure and permeability similar to cartilage, and also have good mechanical properties and biocompatibility. Among them, hydrogel materials have become the focus of research due to their high water absorption, three-dimensional network structure that mimics the extracellular matrix, adjustable biocompatibility, and degradability.

[0004] Hydrogels are mainly formed by high molecular polymers interacting with each other through chemical bond forces or physical binding forces and crosslinking to form crosslinked polymers with a three-dimensional network structure. They contain hydrophilic groups, can rapidly swell in water and retain a large amount of water, but will not dissolve. The structural characteristics of hydrogels such as high water absorption rate, biodegradability, porosity, and biocompatibility are similar to those of the natural extracellular matrix, and they can mimic some of its properties and are widely used in tissue engineering.

[0005] However, a large number of studies have shown that although natural biomaterials such as chitosan and gelatin are the main components of articular cartilage and have good biocompatibility and cartilage induction properties, their mechanical properties are weak and cannot meet the needs of cartilage engineering.

[0006] Therefore, it is necessary to develop new composite hydrogel materials with a three-dimensional porous structure, so that they can overcome the deficiencies of traditional hydrogels for cartilage repair and achieve good cartilage repair effects. Summary of the Invention

[0007] In view of this, the present invention blends chitosan, gelatin, and PVA, and combines chemical crosslinking and physical crosslinking methods to solve the deficiencies of existing hydrogel materials in terms of mechanical properties and biocompatibility. At the same time, hydroxyapatite extracted from grass carp scales is added to promote osteogenesis, improving its application effect in cartilage repair and providing a new choice for the practical application of cartilage repair materials.

[0008] The first aspect of the present invention is to provide a method for preparing a chitosan / gelatin / PVA composite hydrogel, which specifically includes the following steps:

[0009] Mix the chitosan solution, gelatin solution, hydroxyapatite (HAP), and polyvinyl alcohol (PVA) evenly under a water bath condition, then add a crosslinking agent for blending and crosslinking, and defoam to obtain a mixed solution; the mixed solution is dried after cyclic freezing and thawing to obtain the chitosan / gelatin / PVA composite hydrogel.

[0010] Preferably, the content of HAP in the mixed solution is 1 wt.% - 3 wt.% of the total amount of chitosan and gelatin, and the content of PVA in the mixed solution is 50 wt.% - 150 wt.% of the total amount of chitosan and gelatin. More preferably, the content of HAP in the mixed solution is 1 wt.% or 2 wt.% of the total amount of chitosan and gelatin, and the content of PVA is 50 wt.% or 150 wt.% of the total amount of chitosan and gelatin.

[0011] Preferably, the mass ratio of chitosan to gelatin is (1 - 2):(1 - 2). More preferably, the mass ratio of chitosan to gelatin is 1:1.

[0012] Preferably, the crosslinking agent is glutaraldehyde.

[0013] Preferably, the dosage of the crosslinking agent is 0.5 - 2 wt% of the total amount of chitosan, gelatin, and PVA.

[0014] Preferably, the crosslinking temperature is 50°C and the crosslinking time is 2 h.

[0015] Preferably, the water bath temperature is 70°C - 90°C. More preferably, the water bath temperature is 80°C.

[0016] Preferably, the number of cyclic freezing and thawing times is 2 - 4 times, preferably 3 times. Freeze the mixed solution at -20°C for 10 - 16 h, and then thaw it at room temperature for 1 - 4 h to complete one cycle of freezing and thawing. More preferably, the number of cyclic freezing and thawing times is 3 times. Freeze the mixed solution at -20°C for 12 h, and then thaw it at room temperature for 2 h to complete one cycle of freezing and thawing.

[0017] Preferably, the drying temperature is 50°C and the drying time is 12 h.

[0018] The second aspect of the present invention is to provide a chitosan / gelatin / PVA composite hydrogel prepared according to the above method.

[0019] The third aspect of the present invention is to provide an application of a chitosan / gelatin / PVA composite hydrogel as a cartilage repair material, and the chitosan / gelatin / PVA composite hydrogel is the chitosan / gelatin / PVA composite hydrogel described in the above technical solution.

[0020] Compared with the prior art, the beneficial technical effects of the present invention are as follows:

[0021] By blending natural polymer materials (chitosan, gelatin) with a synthetic polymer material (PVA) and adopting a combination of chemical cross-linking (glutaraldehyde) and physical cross-linking (cyclic freeze-thaw method), the present invention effectively makes up for the defects of single materials. The natural materials improve biocompatibility and cell affinity, while PVA significantly enhances the mechanical properties, solving the problems of poor mechanical properties of traditional natural materials or insufficient bio-inertia of synthetic materials.

[0022] The hydrogel prepared by the present invention has a cross-connected three-dimensional porous network structure with a uniform pore size distribution (5–10 μm) and interconnected pores, which is beneficial for cell infiltration, nutrient transport and metabolite excretion, and better meets the structural requirements of cartilage repair for scaffold materials.

[0023] The present invention clarifies the influence of different factors on the properties of the hydrogel. Among them, the optimal formula for thermal stability (2% glutaraldehyde, 1% HAP, 150% PVA) shows the highest thermal stability (T 5% reaches 121.1 °C, T 50% reaches 360.2 °C) in thermogravimetric analysis; the optimal formula for mechanical properties (1% glutaraldehyde, 2% HAP, 150% PVA) has a tensile strength of 0.44 MPa, which is significantly higher than that of traditional natural hydrogels; the optimal formula for water absorption performance (0.5% glutaraldehyde, 1% HAP, 50% PVA) has a water absorption rate as high as 73.6%, improving the lubrication performance.

[0024] The composite hydrogel of the present invention has both mechanical strength, thermal stability, high water absorption and biocompatibility, and can flexibly adjust the formula according to different repair requirements (such as high mechanical strength is required for load-bearing parts, and high water absorption is required for joint lubrication), providing a multifunctional material basis for cartilage tissue engineering. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The present invention will be further described below in conjunction with the drawings.

[0026] Figure 1 Scanning electron microscope observation results of chitosan / gelatin / PVA composite hydrogels with different ratios, where A is DN-1 hydrogel, B is DN-3 hydrogel, and C is DN-9 hydrogel;

[0027] Figure 2 Thermogravimetric curves of chitosan / gelatin / PVA composite hydrogels with different ratios;

[0028] Figure 3 Tensile property test results of chitosan / gelatin / PVA composite hydrogels with different ratios;

[0029] Figure 4 Water absorption rate of chitosan / gelatin / PVA composite hydrogels with different ratios. Specific implementation manners

[0030] Next, the technical solutions of the present invention will be clearly and completely described in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts shall fall within the protection scope of the present invention.

[0031] The first aspect of the present invention is to provide a preparation method of a chitosan / gelatin / PVA composite hydrogel, which specifically includes the following steps:

[0032] S1. Dissolve chitosan in an acetic acid solution to obtain a chitosan solution;

[0033] S2. Dissolve gelatin in deionized water to obtain a gelatin solution;

[0034] S3. Mix the chitosan solution, gelatin solution, HAP and PVA evenly under a water bath condition, then add a crosslinking agent for co - blending crosslinking, and defoam to obtain a mixed solution;

[0035] S4. Dry the mixed solution after cyclic freeze - thawing to obtain a chitosan / gelatin / PVA composite hydrogel.

[0036] The concentration of the acetic acid solution in the present invention is 1 wt.% - 5 wt.%, preferably 5 wt.%; the material ratio of chitosan to the acetic acid solution is 1:(10 - 20), preferably 1 g:15 mL; the material ratio of gelatin to deionized water is 1:(30 - 60), preferably 1 g:45 mL; the content of HAP in the mixed solution is 1 wt.% - 3 wt.% of the total amount of chitosan and gelatin, preferably 1 wt.% or 2 wt.%, the content of PVA is 50 wt.% - 150 wt.% of the total amount of chitosan and gelatin, preferably 50 wt.% or 150 wt.%, the mass ratio of chitosan to gelatin is (1 - 2):(1 - 2), preferably 1:1; the cross-linking agent is glutaraldehyde, and the dosage of the cross-linking agent is 0.5 - 2 wt% of the total amount of chitosan, gelatin and PVA; the cross-linking temperature is 50 °C and the cross-linking time is 2 h; the water bath temperature is 70 °C - 90 °C, preferably 80 °C; the number of cycles of freezing and thawing is 2 - 4 times, preferably 3 times. The mixed solution is frozen at -20 °C for 10 - 16 h and then thawed at room temperature for 1 - 4 h to complete one cycle of freezing and thawing; preferably, the mixed solution is frozen at -20 °C for 12 h and then thawed at room temperature for 12 h to complete one cycle of freezing and thawing; the drying temperature is 50 °C and the drying time is 12 h.

[0037] The present invention does not strictly limit the defoaming method, and vacuum defoaming (vacuum degree ≤ 0.1 MPa, time 10 - 30 min), stirring defoaming (rotation speed 2000 - 5000 rpm, time 5 - 15 min), ultrasonic defoaming (frequency 40 kHz, power 100 W, treatment 10 - 20 min), stirring defoaming (rotation speed 100 - 300 rpm, time 10 - 30 min) or static natural defoaming (standing at room temperature for 12 - 24 h) can be used alone or in combination. The specific parameters can be adjusted according to the situation of the mixed solution.

[0038] In some specific embodiments of the present invention, the HAP is HAP extracted from grass carp scales. The present invention does not strictly limit the method for extracting HAP from grass carp scales, and conventional HAP extraction methods in the art can be used in the present invention.

[0039] The second aspect of the present invention is to provide a chitosan / gelatin / PVA composite hydrogel prepared according to the above method.

[0040] The third aspect of the present invention is to provide an application of the chitosan / gelatin / PVA composite hydrogel as a cartilage repair material, and the chitosan / gelatin / PVA composite hydrogel is the chitosan / gelatin / PVA composite hydrogel described in the above technical solution.

[0041] The application method of the chitosan / gelatin / PVA composite hydrogel in the present invention is as follows:

[0042] The hydrogel is processed according to requirements (such as cell loading, drug loading, etc.), trimmed and then implanted into the cartilage defect for fixation.

[0043] To further illustrate the present invention, the following detailed description is provided through the following examples. All raw materials used in the following examples of the present invention are commercially available.

[0044] Unless otherwise specified, all experiments were repeated 3 times. ANOVA (analysis of variance) and Duncan's multiple comparison analysis were performed using SPSS 21.0. The results are expressed as mean ± standard deviation, and significant differences are indicated when P < 0.05.

[0045] Example 1 A method for preparing a chitosan / gelatin / PVA composite hydrogel, the steps are as follows:

[0046] S1. Dissolve 1 g of chitosan in 15 mL of acetic acid solution with a concentration of 5 wt.%, to obtain a chitosan solution;

[0047] S2. Add 1 g of gelatin to 45 mL of deionized water, and stir with a magnetic stirrer at 80 °C until a transparent solution is obtained, to obtain a gelatin solution;

[0048] S3. Mix and blend the chitosan solution, gelatin solution, different amounts of HAP and different amounts of PVA under the condition of an 80 °C water bath, then add different amounts of cross-linking agent and co-blend and cross-link at 50 °C for 2 h, and stir and defoam at 200 rpm for 1 h to obtain a mixed solution;

[0049] The dosages of the HAP and PVA are adjusted according to the total amount of chitosan and gelatin; the dosage of the cross-linking agent is adjusted according to the total amount of chitosan, gelatin, and PVA;

[0050] For example, in combination 1, the PVA content is 50%, indicating that the dosage of PVA is 50% of the total amount of chitosan and gelatin, that is, 1 g; the HAP content is 1%, indicating that the dosage of HAP is 1% of the total amount of chitosan and gelatin, that is, 0.02 g; the cross-linking agent content is 0.5%, indicating that the dosage of the cross-linking agent is 0.5% of the total amount of chitosan, gelatin, and PVA, that is, 0.015 g; the same applies to the other groups;

[0051] S4. After the mixed solution is subjected to 3 cycles of freeze-thawing (-20 °C for 12 h, room temperature thawing for 2 h), dry at 50 °C for 12 h to obtain a chitosan / gelatin / PVA composite hydrogel.

[0052] The orthogonal test design is as follows:

[0053] Table 1 Orthogonal test table of three factors and three levels

[0054]

[0055] Taking the contents of crosslinking agent glutaraldehyde, HAP (HAP), and PVA (PVA) as the experimental factors of the orthogonal experiment, an orthogonal experiment table with three factors and three levels is set as shown in Table 1, where the percentage is the percentage of the total content of gelatin and chitosan.

[0056] Test Example 1 Electron Scanning Microscope Characterization (SEM)

[0057] The microtopographies of the hydrogels with representative properties in Group 1, Group 3, and Group 9 were characterized by scanning electron microscopy, denoted as DN-1, DN-3, and DN-9 respectively. The scanning voltage was 10 kv. The specific method is as follows: Cut a small piece of dry hydrogel and brittle fracture it in liquid nitrogen to obtain a cross-sectional sample for SEM. After placing the sample in a plastic petri dish and freeze-drying it in a freeze-dryer for 12 h, stick it on a metal sample stage with conductive glue. After sputtering gold treatment with an ion sputtering instrument, perform surface morphology characterization of the material on the scanning electron microscope. The results are as Figure 1 shown.

[0058] From Figure 1 it can be seen that the chitosan / gelatin / PVA composite hydrogels with different ratios have different internal structures. Among them, DN-1 has no obvious pore structure, while DN-3 and DN-9 have relatively obvious three-dimensional network pore diameter structures. Their distributions are uniform, with different sizes. Small pores are distributed around the large pores and are well interconnected. The diameter of the large pores is about 5 - 10 μm, and the thickness of the pore walls varies. Among them, DN-9 is thicker and the pore walls of DN-3 are thinner. It can be seen that the composite hydrogel of the present invention exhibits a porous structure, which is beneficial for cells to infiltrate and migrate into the interior of the scaffold, and is more beneficial for cartilage repair.

[0059] Test Example 2 Thermogravimetric Test (TG)

[0060] The thermal stability analysis of the composite hydrogel material prepared in Example 1 was carried out in a microcomputer differential thermal balance. The specific method is as follows: Weigh 7 - 9 mg of the sample and place it in a crucible. The sample is always in an N2 atmosphere. Set the gas flow to 40 mL / min, the heating rate of the microcomputer differential thermal balance to 10 °C / min, and the temperature range to 0 °C - 600 °C. Obtain the experimental data and explore the differences in the thermal stability performance of materials with different formulations by analyzing the changes in the TG curve. The results are shown in Table 2 and Figure 2 shown.

[0061] Table 2 Temperatures corresponding to 5%, 10%, and 50% weight loss of the sample

[0062]

[0063] Thus, it can be seen that the T 5% , T 10% and T 50%All are the highest, that is, the chitosan / gelatin / PVA composite hydrogel with a glutaraldehyde crosslinking agent content of 2%, a HAP content of 1%, and a PVA content of 150% has the best thermal stability. Among them, T 5% , T 10% , T 50% are the temperatures corresponding to weight losses of 5%, 10%, and 50% respectively.

[0064] Test Example 3 Tensile Property Test

[0065] The mechanical properties of the composite hydrogel of Example 1 were tested using a universal material testing machine (Suns UTM2502 universal testing machine). The specific method is as follows: Cut the sample into a cuboid of 30 mm × 10 mm × 2 mm and place it on the tensile fixture. Conduct the experiment at a loading speed of 5 mm / min. According to the experimental results, discuss the influence of different formulations on the mechanical properties of the sample bars.

[0066] The test results are shown in Table 3 and Figure 3 as follows.

[0067] Table 3 Orthogonal Test Results of Tensile Properties

[0068]

[0069] As a scaffold material for osteochondral defect implantation, the tensile strength should be an important evaluation factor for the scaffold material. Because the scaffold needs to be able to withstand a certain load when implanted in the defect site, so as to maintain normal physiological activities. From Table 3 and Figure 3 it can be seen that for Group 5, that is, the chitosan / gelatin / PVA composite hydrogel with a glutaraldehyde crosslinking agent content of 1%, a HAP content of 2%, and a PVA content of 150% has the best mechanical properties, and the increase in the PVA content in the hydrogel can increase its mechanical strength.

[0070] Test Example 5 Water Absorption Test

[0071] The water absorption rate of the composite hydrogel material prepared in Example 1 was measured by the weighing method. The specific method is as follows: Cut a small section of the composite hydrogel, freeze-dry it and weigh its mass. After placing it in water for 24 h, weigh the sample, and calculate the water absorption rate (W) of the sample through Equation 2-2:

[0072]

[0073] In the formula, W dry is the mass of the freeze-dried hydrogel, and W wet is the mass of the freeze-dried hydrogel after absorbing water for 24 h.

[0074] The results are shown in Table 4 and Figure 4 as follows.

[0075] Orthogonal test results of water absorption rate in Table 4

[0076]

[0077] The water absorption of the hydrogel is crucial for its lubrication performance. To determine the effects of the dosages of PVA, HAP, and glutaraldehyde during the preparation process on the hydrogel, the water absorption of nine groups of composite hydrogels with different ratios set in the orthogonal test was measured in this paper. Calculations show that glutaraldehyde, HAP, and PVA have certain effects on the water resistance of the material. Among them, the chitosan / gelatin / PVA composite hydrogel with a glutaraldehyde content of 0.5%, an HAP content of 1%, and a PVA content of 50% has the best water absorption performance, and the content of PVA has the greatest impact on the water absorption performance of its hydrogel. This may be because it contains a large number of hydrophilic groups - hydroxyl groups inside, making it have good hydrophilicity. In this experiment, the hydrogel was soaked in an aqueous solution and placed under the same conditions. Therefore, conditions such as temperature, pressure, and solvent remain unchanged, and only the effects of the contents of glutaraldehyde, HAP, and PVA on the water absorption behavior of the hydrogel are discussed.

[0078] In summary, through physical and chemical cross-linking, the present invention obtains a hydrogel with a cross-linked and interconnected three-dimensional network structure. Among them, the chitosan / gelatin / PVA composite hydrogel with a glutaraldehyde content of 2%, an HAP content of 1%, and a PVA content of 150% has the best thermal stability; the chitosan / gelatin / PVA composite hydrogel with a glutaraldehyde content of 1%, an HAP content of 2%, and a PVA content of 150% has the best mechanical properties; the chitosan / gelatin / PVA composite hydrogel with a glutaraldehyde content of 0.5%, an HAP content of 1%, and a PVA content of 50% has the best water absorption performance.

[0079] Comparative Example 1

[0080] Same as Example 1, Group 7, the difference is that: chitosan was not used during the gel preparation process.

[0081] After testing, the gel T 5% 、T 10% 、T 50% obtained from this comparative example are 109.1 °C, 135.7 °C, 321.9 °C respectively, the tensile strength is 0.21 MPa, and the water absorption rate is 42.6%.

[0082] Comparative Example 2

[0083] Same as Example 1, Group 7, the difference is that: gelatin was not used during the gel preparation process.

[0084] After testing, the gel T 5% 、T 10% 、T 50%They are 112.9 °C, 143.5 °C, 332.6 °C respectively, the tensile strength is 0.18 MPa, and the water absorption rate is 43.9%.

[0085] Comparative Example 3

[0086] Same as Example 1, Combination 5, the difference is that cyclic freezing and thawing were not carried out.

[0087] After testing, the gel T obtained in this comparative example 5% 、T 10% 、T 50% They are 64.9 °C, 77.1 °C, 321.9 °C respectively, the tensile strength is 0.29 MPa, and the water absorption rate is 51.1%.

[0088] Comparative Example 4

[0089] Same as Example 1, Combination 1, the difference is that during the 3 cycles of freezing and thawing, the freezing temperature was -40 °C.

[0090] After testing, the gel T obtained in this comparative example 5% 、T 10% 、T 50% They are 66.3 °C, 82.1 °C, 117.3 °C respectively, the tensile strength is 0.13 MPa, and the water absorption rate is 53.7%.

[0091] Comparative Example 5

[0092] Same as Example 1, Combination 2, the difference is that glutaraldehyde was replaced with an equal amount of tannic acid.

[0093] After testing, the gel T obtained in this comparative example 5% 、T 10% 、T 50% They are 103.1 °C, 132.2 °C, 327.1 °C respectively, the tensile strength is 0.19 MPa, and the water absorption rate is 51.6%.

[0094] The above-described embodiments merely represent several implementation manners of the present invention. Their descriptions are relatively specific and detailed, but they should not be construed as limiting the scope of the invention patent. It should be noted that for those of ordinary skill in the art, without departing from the concept of the present invention, several modifications and improvements can still be made, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the present invention patent shall be subject to the appended claims.

Claims

1. A preparation method of a chitosan / gelatin / PVA composite hydrogel, characterized in that, It includes the following steps: Mix the chitosan solution, gelatin solution, hydroxyapatite HAP, and polyvinyl alcohol PVA solution evenly under water bath conditions, then add a cross-linking agent for cross-linking and defoaming to obtain a mixed solution; after cyclic freezing and thawing of the mixed solution, a chitosan / gelatin / PVA composite hydrogel is obtained. The cross-linking agent is glutaraldehyde. The number of cyclic freezing and thawing times is 2 - 4 times. Freeze the mixed solution at -20 °C for 10 - 16 h, and then thaw it at room temperature for 1 - 4 h to complete one cycle of freezing and thawing.

2. The preparation method according to claim 1, wherein The content of HAP in the mixed solution is 1 wt.% - 3 wt.% of the total amount of chitosan and gelatin.

3. The preparation method according to claim 1, wherein, The content of PVA in the mixed solution is 50 wt.% - 150 wt.% of the total amount of chitosan and gelatin.

4. The preparation method according to claim 1, characterized in that, The mass ratio of chitosan to gelatin is (1 - 2):(1 - 2).

5. The preparation method according to claim 1, wherein The water bath temperature is 80 °C.

6. The preparation method according to claim 1, characterized in that, The cross-linking temperature is 50 °C and the cross-linking time is 2 h.

7. The preparation method according to claim 1, wherein, The number of cyclic freezing and thawing times is 3 times.

8. The preparation method according to claim 1, wherein, Freeze the mixed solution at -20 °C for 12 h, and then thaw it at room temperature for 2 h to complete one cycle of freezing and thawing.

9. A chitosan / gelatin / PVA composite hydrogel, characterized in that, The chitosan / gelatin / PVA composite hydrogel is prepared by the method according to any one of claims 1 - 8.

10. Use of a chitosan / gelatin / PVA composite hydrogel as a cartilage repair material, characterized in that, The chitosan / gelatin / PVA composite hydrogel is a chitosan / gelatin / PVA composite hydrogel according to claim 9.